316 Rising solar radiation in the late morning increases thermoregulatory strain during 2-h football training under a clear sky in the heat. (3rd March 2020) - Otani, Hidenori; Goto, Takayuki; Goto, Heita; Hosokawa, Yuri; Shirato, Minayuki
Abstract : Background: No study investigated the time-of-day effects of solar radiation on thermoregulatory strain during high-intensity exercise in the heat outdoors. Objective: To investigate the diurnal effects of variations in solar radiation associated with changing solar elevation angle on thermoregulatory strain in high school athletes participating in 2-h football training under a clear sky in the heat. Design: Field trial; Crossover study Setting: High school sports Patients (or Participants): Ten male high school football players. Interventions (or assessment of risk factors): Participants completed two 2-h football training sessions under a clear sky in the heat of summer. These sessions were commenced at 09:00 h (AM) and 16:00 h (PM) on separate days. Main outcome measurements: Body temperature; Heart rate; Perception Results: Solar radiation and elevation angle were higher in AM (820–1070 W·m −2 and 45–69°) than PM (620–110 W·m −2 and 34–10°: both P <0.001). Neither ambient temperature (AM 29–32°C; PM 31–31°C) nor wet-bulb globe temperature (WBGT) was different between trials. Although mean skin temperature was not different between trials, infrared tympanic temperature was higher during exercise in AM than PM ( P <0.001). Heart rate ( P <0.01) and body heat gain from the sun ( P <0.001) were greater in AM than PM. Dry heat loss was smaller but evaporative heat loss was greater in AM than PM (both P <0.001). Thermal sensation and rating of perceived exertion were similar between trials. Total distance and distance covered by walking, jogging and running were less in AM than PM ( P <0.01). Conclusions: Under similar ambient temperature and WBGT conditions, thermoregulatory strain during a 2-h football training under a clear sky in the heat was higher during late morning when solar radiation and elevation angle were greater compared to the afternoon session when falling solar radiation and elevation angle were observed. This suggests that the risk for heat illness is higher in the late morning than afternoon during high-intensity exercise under a clear sky in the heat.